2019
DOI: 10.1590/1980-549720190015.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Income inequalities in oral health and access to dental services in the Brazilian population: National Health Survey, 2013

Abstract: Introduction: Despite the improvement in oral health conditions observed in the Brazilian population, there are still high social inequalities that must be monitored. Objective: To evaluate income inequality in oral hygiene practices, oral health status and the use of dental services in the adult and senior Brazilian population. Methods: Data from the National Health Survey conducted in 2013 (Pesquisa Nacional de Saúde - PNS 2013) were used for the population aged 18 years old or older. Results: Inequal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 31 publications
4
43
0
18
Order By: Relevance
“…The proportion of older adults who accessed dental services within the previous year was relatively small (30.5%). This figure is consistent with findings from the overall population of Brazilian older adults (29.4%) 28 . Higher rates of utilisation of dental services within the previous year were observed among the elders from the United States (62.4%), 29 Japan (57%), 30 Israel (44.4%), 31 France (46,2%), 32 older Korean immigrants living in the United States (62%) 33 and older adults from a city in the South of Brazil (38.3%) 34 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The proportion of older adults who accessed dental services within the previous year was relatively small (30.5%). This figure is consistent with findings from the overall population of Brazilian older adults (29.4%) 28 . Higher rates of utilisation of dental services within the previous year were observed among the elders from the United States (62.4%), 29 Japan (57%), 30 Israel (44.4%), 31 France (46,2%), 32 older Korean immigrants living in the United States (62%) 33 and older adults from a city in the South of Brazil (38.3%) 34 .…”
Section: Discussionsupporting
confidence: 92%
“…This figure is consistent with findings from the overall population of Brazilian older adults (29.4%). 28 Higher rates of utilisation of dental services within the previous year were observed among the elders from the United States (62.4%), 29 Japan (57%), 30 Israel (44.4%), 31 France (46,2%), 32 older Korean immigrants living in the United States (62%) 33 and older adults from a city in the South of Brazil (38.3%). 34 Conversely, a study with data from 66 countries found that the average rates of utilisation of dental services within the previous year among older adults aged 60-69 years and 70 years or older were of 18% and 14.1%, respectively.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 93%
“…Conversely, the suspension of elective dental procedures might facilitate the deterioration of the oral health of the population, leading to irreparable damages and consequently reducing the quality of life of these subjects ( 18 ). Oral health and inequalities are a recognized major problem in the world, and such conditions is generally linked with lower-income segments of the population ( 30 ). Thus, the reduction of elective procedures provided by the national public health system observed in our study could reflect the impact that is occurring throughout the globe.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable limitation of the present study, related with the absence of a proper randomization, is the presence of a selection bias related with the possible higher socioeconomic status of subjects treated with CA rather than MB considering that there was a reported association between oral hygiene level and socioeconomic status [24].…”
Section: Plos Onementioning
confidence: 92%